Epidemiology of parvovirus B19 and anemia among kidney transplant recipients: A meta-analysis - Charat Thongprayoon (2020)
© 2020 Urology Annals | Published by Wolters Kluwer-Medknow. Background: Persistent anemia has been described in kidney transplant (KTx) recipients with parvovirus B19 virus infection. However, the epidemiology of parvovirus B19 and parvovirus B19-related anemia after KTx remains unclear. We conducted this systematic review (1) to investigate the incidence of parvovirus B19 infection after KTx and (2) to assess the incidence of parvovirus B19 among KTx patients with anemia. Materials and Methods: A systematic review was conducted in EMBASE, MEDLINE, and Cochrane databases from inception to March 2019 to identify studies that reported the incidence rate of parvovirus B19 infection and/or seroprevalence of parvovirus B19 in KTx recipients. Effect estimates from the individual studies were extracted and combined using random-effects, generic inverse variance method of DerSimonian and Laird. The protocol for this systematic review is registered with PROSPERO (no. CRD42019125716). Results: Nineteen observational studies with a total of 2108 KTx patients were enrolled. Overall, the pooled estimated seroprevalence of parvovirus B19 immunoglobulin G was 62.2% (95% confidence interval [CI]: 45.8%-76.1%). The pooled estimated incidence rate of positive parvovirus B19 DNA in the 1st year after KTx was 10.3% (95% CI: 5.5%-18.4%). After sensitivity analysis excluded a study that solely included KTx patients with anemia, the pooled estimated incidence rate of positive parvovirus B19 DNA after KTx was 7.6% (95% CI: 3.7%-15.0%). Among KTx with anemia, the pooled estimated incidence rate of positive parvovirus B19 DNA was 27.4% (95% CI: 16.6%-41.7%). Meta-regression analysis demonstrated no significant correlations between the year of study and the incidence rate of positive parvovirus B19 DNA (P = 0.33). Egger's regression asymmetry test was performed and demonstrated no publication bias in all analyses. Conclusion: The overall estimated incidence of positive parvovirus B19 DNA after KTX is 10.3%. Among KTx with anemia, the incidence rate of positive parvovirus B19 DNA is 27.4%. The incidence of positive parvovirus B19 DNA does not seem to decrease overtime.